Antibiotic use in heavy pigs: Comparison between urine and muscle samples from food chain animals analysed by HPLC-MS/MS. (15th November 2017) - Chiesa, Luca Maria; Nobile, Maria; Panseri, Sara; Arioli, Francesco
Highlights: Antibiotic overuse in pig breeding is of concern, due to antibiotic resistance onset. Despite being invasive, muscle is usually the matrix used for the residue control. Urine could allow improved monitoring, as on-farm sample collection is feasible. A multiclass method for antibiotics detection in urine and muscle was validated. Its application to 43 paired urine and muscle samples was effective. Abstract: The antibiotic overuse in zoothechnics, due to prophylactic and therapeutic treatments, or to their growth-promoting activity, is a major cause for the onset of widespread antibiotic resistance. Of particular relevance to this study, is the antibiotic abuse in pig breeding. Despite the comprehensive literature on residue controls in pig muscle, data on pig urine, a non-invasive, on-farm collectable matrix, are lacking. Therefore, we validated an HPLC-MS/MS method to detect 29 antimicrobials from eight classes and applied it to 43 anonymous pig urine and muscle paired samples and fulfilled the parameters in agreement with the Commission Decision 2002/657/UE. The analytical limits were moreover much lower than the maximum residue limits (MRLs) required by the Commission Regulation 37/2010/UE. In the samples, antibiotics were usually detected at higher frequencies and concentrations in urine than muscle. Urine proved a useful tool to detect antibiotic administration and their excessive use in pig farming is depicted.